Russia’s Participation in the Development of Transport and Logistics Highways of the EAEU Member States - A. Sh. Agaeva; Sh. A. Idrisov (Евразийская интеграция: экономика, право, политика, 2024)
Aim. An overview analysis of the prospects for trade and economic relations in the EAEU, the SCO countries and other interested states, coupled with interests in the geo-economic and geopolitical Eurasian space in the conditions of artificial escalation of local tensions by the collective West.Tasks. Search and evaluation of optimal routes for the development of traditional and new transport and logistics highways, their branched corridors from the perspective of strengthening economic integration agreements, security and interaction of the Eurasian Union with the SCO countries.Methods. The article uses methodological tools of spatial economics, economic, geographical and geopolitical analysis of the interests of states, analysis and synthesis of interests and synergy of interests of the participating states of global Eurasian projects.Conclusions. The study showed the possibilities of new and old transport magistral (the highway) systems (TMS), both through Kazakhstan and through the development of a unique alternative — the Northern Sea Route (NSR) with the construction of a completely new infrastructure and their maintenance. The issues of TMS on the BAM and Trans-Siberian railway were touched upon. An assessment of alternatives to TMS in terms of cost and time is given. The potential opportunities of the expanding TMS and cargo traffic along the Caspian-Caspian corridor, both overland from the east (Turkmenistan — Kazakhstan — Russia) and the western shore of the Caspian Sea (Iran — Azerbaijan — Russia), as well as along waterways along the same “North — South” corridor, are indicated.Results. An assessment of effective routes has been carried out; strategic objectives have been identified for newly opened transport and logistics highways, which are defined as “new lye routes” through the territories of the EAEU and neighboring interested states (China, India, Pakistan, Afghanistan, Iran, etc.), which gradually plan to enter into closer relations from participating observers relations in the international division of labor.